The Impact of Work-Life Balance and Burnout on Employee Performance with Job Satisfaction as an Intervening Variable among Generation Z Employees in Bekasi Regency - Afifah Nur Zahra; Novi Fitria Hermiati (Jurnal Ilmu Manajemen Profitability, 2023)
Generation Z refers to individuals born between 1995 and 2010. Growing up in the midst of technological advancements, Generation Z possesses distinct mindsets and habits compared to previous generations, which consequently influences their perspectives on the workforce. This research aims to examine the effects of Work-Life Balance and Burnout on Employee Performance, with Job Satisfaction as the mediating variable, among Generation Z employees in Bekasi Regency. The sampling method employed in this study is non-probability sampling, specifically purposive sampling, with a sample size of 120 respondents determined using the Lemeshow formula. The participants of this research consist of Generation Z employees in Bekasi Regency. The methodology employed in this study is Structural Equation Modeling (SEM) analysis conducted with Lisrel 8.8 software. The findings indicate that Work-Life Balance does not significantly impact Employee Performance, Burnout does not significantly influence Employee Performance, Burnout does not significantly affect Job Satisfaction, Work-Life Balance significantly affects Job Satisfaction, Job Satisfaction significantly impacts Employee Performance, and Job Satisfaction mediates the relationship between Work-Life Balance and Employee Performance, as well as Burnout and Employee Performance.